"Creation out of nothing" – A problematic assumption: biblical, metaphysical and scientific perspectives - Nürnberger, Klaus (HTS teologiese studies, 2021)
Science, technology, commerce and consumerism have set humankind on a trajectory towards a catastrophe of inestimable proportions. To respond appropriately to this danger, theology must replace obsolete contextualisations of its message with currently relevant ones. ‘Creation out of nothing’ is a case in point. Will God create a new and perfect world ‘out of nothing’ after we have messed up the one we have? Probably not! In Part I, I show that ‘creation out of nothing’ is not a relevant issue in the biblical tradition. In Part II, I argue that the concept is based on the unsupported metaphysical postulate of ‘divine perfection’. In Part III, I try to find an equivalent for the concept in science that theology could link up with. ‘Creation’ can be equated with a cosmic evolution proceeding in levels of emergence. But ‘out of nothing’ cannot be supported by science. Even at the most fundamental level, energy and the way it operates, are presupposed. At lower levels, the process is guided by causality and (embedded) contingency. Intentionality and agency only appear at the personal and social levels. Dealing with existential needs, faith (appropriately) intuits a personal transcendent Source and Destiny of reality, but (inappropriately) absolutizes the personal at the expense of the impersonal aspects of reality. The laws of nature are also of God; they are essential; they are valid. They leave sufficient space for novelty and agency, but God works as much through regularity as through contingency.Contribution: The dynamic nature of the biblical tradition demands constant re-contextualisations of its central message. ‘Creation out of nothing’ is part of the contextualisation of the message into the ancient Hellenistic worldview, which does not fit into the modern scientific worldview and must be replaced with a contemporarily more appropriate alternative.